Hospital Antibiotics Usage: Environmental Hazard and Promotion of Antibiotic Resistant Bacteria - Chamkal, N.; Lhlou, I.; Bandadi, L.; Ounine, K. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Hospitals constitute a particular source of drug residues emission, especially antibiotics considered as the most critical therapeutic classes used in hospitals. Thus, the hospital wastewater can widely spread both types of emerging pollutants, antibiotic residues and antibiotic resistance bacteria. For this reason, antibiotics usage must be monitored. This study was conducted to investigate potential antibiotic compounds which can present potential environmental hazard and promote antibiotic resistance. Methods. The consumption-based approach was adopted to calculate predicted antibiotic concentrations in hospital wastewaters. In the process, we assessed the antibiotics potential environmental hazard, with the hazard quotient between predicted concentrations and predicted no effect concentrations intended to be protective of ecological species. In order to evaluate the hospital contribution to antibiotic resistance bacteria promotion, we also compared predicted concentrations with predicted no effect concentrations as theoretical selective resistance bacteria. Results. The highest expected concentrations in hospital wastewater were found for Penicillins and Cephalosporins being the most prescribed antibiotics in our context. We noted that among this class, Ampicillin is the most hazardous compound followed by Imipenem and Gentamicin as exclusive hospital use antibiotics, in spite of their low consumption. The results showed also that Ampicillin, Amoxicillin, and Ceftriaxone had a high ratio of potential antibiotic resistance bacteria promotion, confirming the correlation found previously between abundance of resistant bacteria and the corresponding effluent antibiotic concentrations. Nevertheless, the promotion of resistance selection can also be attributed to Imipenem and Ciprofloxacin as little-used antibiotics and occur at low to moderate levels in hospital wastewater. Conclusion. This study identified the profile antibiotics consumption and their potential environmental hazard contribution and antibiotic resistant bacteria promotion. It can help decision-makers make appropriate management decisions, especially preventive measures related to antibiotic use pattern, as neither dilution nor treatment can eliminate antibiotic residues and antibiotic resistance genes.